Dinamika Pembelajaran Komunikasi Reseptif Anak dengan Autism Spectrum Disorder (ASD) melalui Penggunaan Media Flash Card Fauna - Nur Anis; Risbon Sianturi; Aini Loita (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Receptive communication is one of the developmental domains that commonly presents challenges for children with Autism Spectrum Disorder (ASD). Although previous studies have demonstrated the effectiveness of visual media in improving communication skills among children with ASD, most have primarily focused on intervention outcomes, while the learning dynamics during media implementation remain underexplored. This study aimed to describe the dynamics of receptive communication learning through the use of Fauna Flash Cards for a child with ASD. A qualitative intrinsic case study was conducted at RA Raihan Persis 27 involving an eight-year-old child diagnosed with ASD. Data were collected through classroom observations, in-depth interviews, and documentation, and analyzed using thematic analysis with source and technique triangulation to ensure data credibility. The findings revealed that prior to the intervention, the child experienced difficulties in understanding verbal instructions, maintaining attention, and responding consistently to learning stimuli. The Fauna Flash Cards were implemented progressively through picture introduction, repeated instructions, prompting, simple games, and positive reinforcement, resulting in improved attention, picture recognition, and the emergence of simple vocabulary. The novelty of this study lies in its in-depth exploration of learning dynamics, including teacher–child interactions, children's responses, and contextual factors influencing the implementation of visual media in receptive communication learning. Scientifically, this study enriches the literature on visual media-based receptive communication learning in inclusive early childhood education. Practically, the findings provide guidance for teachers, therapists, and parents to implement Fauna Flash Cards systematically and adaptively according to the learning characteristics of children with ASD